Place-based, intersectional variation in caregiving patterns and health outcomes among informal caregivers in the United States - Cohen, Steven A.; Nash, Caitlin C.; Greaney, Mary L. (Frontiers in Public Health, 2024)
Informal caregiving is a critical component of the healthcare system despite numerous impacts on informal caregivers' health and well-being. Racial and gender disparities in caregiving duties and health outcomes are well documented. Place-based factors, such as neighborhood conditions and rural-urban status, are increasingly being recognized as promoting and moderating health disparities. However, the potential for place-based factors to interact with racial and gender disparities as they relate to caregiving attributes jointly and differentially is not well established. Therefore, the primary objective of this study was to jointly assess the variability in caregiver health and aspects of the caregiving experience by race/ethnicity, sex, and rural-urban status. The study is a secondary analysis of data from the 2021 and 2022Behavioral Risk Factor Surveillance System (BRFSS) from the Centers for Disease Control and Prevention. Multivariable logistic regression or Poisson regression models assessed differences in caregiver attributes and health measures by demographic group categorized by race/ethnicity, sex, and rural-urban status. Respondents from rural counties were significantly more likely to report poor or fair health (23.2% vs. 18.5%), have obesity (41.5% vs. 37.1%), and have a higher average number of comorbidities than urban caregivers. Overall, rural Black male caregivers were 43% more likely to report poor or fair health than White male caregivers (OR 1.43, 95% CI 1.21, 1.69). Urban female caregivers across all racial groups had a significantly higher likelihood of providing care to someone with Alzheimer's disease than rural White males (p < 0.001). Additionally, there were nuanced patterns of caregiving attributes across race/ethnicity*sex*rural-urban status subgroups, particularly concerning caregiving intensity and length of caregiving. Study findings emphasize the need to develop and implement tailored approaches to mitigate caregiver burden and address the nuanced needs of a diverse population of caregivers.